Pembuatan Poliuretan Sebagai Bahan Pelapis Besi Dengan Pengisi Cangkang Kulit Telur - Iqbal, Rahmat; Sami, Muhammad; Zaimahwati, Zaimahwati (Jurnal Riset, Inovasi, Teknologi & Terapan, 2023)
Research on the manufacture of polyurethane as an iron coating material with an eggshell filler has been done. The purpose of this study was to determine the effect of eggshell weight as an additive on the preparation of polyurethane as an iron coating material and to determine the weight effect of Methylene Diphenyl Diisocyanate (MDI) on the manufacture of polyurethane as an iron coating material with an eggshell filler. By mixing Jatropha oil polyols, Methylene Diphenylene Diisocyianate (MDI), and eggshell, then applied to an iron plate. Polyurethane coatings formed in the analysis of thermal adhesion properties of coatings, Thermal (TGA), functional groups (FT-IR), crystal structures (XRD), and coating morphology (SEM). The results obtained which in addition to the ratio of polyol: isocyanate: eggshell shell of 7: 3: 5% obtained the best results that have the strongest adhesion and has a good mixing structure, and has a heat resistance of 300 0C